Determinants Of Ethical Sensitivity Among Malaysian Accounting Students - Jaspal Singh (Universiti Sains Islam Malaysia, 2024)
Accounting is part of everyone’s life and affects all stakeholders who are the users of the accounting information. Organisations are created to serve stakeholders and governments to govern, regulate and safe guard the interests of these stakeholders. Accounting frequently experiences behavioural issues and human governance which is a subset of corporate governance is addressed in this study to examine the individual’s ethical sensitivity and its predictors. This study explores the level of ethical sensitivity and its relationship with religiosity, ethical orientation, gender and academic performance among final year accounting students in Malaysia. This study addresses the lack and the need to inculcate religiously orientated topics to be embedded and inculcated in the syllabi of bachelor of accounting. A mixed method research is applied in this study where questionnaires are administered to final year undergraduate accounting students at selected public and private universities in Malaysia for quantitative method and interview of expert panel for qualitative method. This study utilised Shaub’s (1989) ethical sensitivity questionnaire to measure ethical sensitivity, Allport’s Religiosity Orientation Scale to measure religiosity and Forsyth’s Ethics Position Questionnaire to measure ethical intention. Students are found to be ethically sensitive and by using Binary Logistic Regression, it is concluded that ethical sensitivity is influenced by intrinsic religiosity, idealism and relativism but not influenced by gender, academic performance, social extrinsic religiosity and personal extrinsic religiosity. Similar outcomes are derived from the six interviewees that is analysed using King’s (2004) template analysis method to triangulate the results derived from quantitative method. The Institutions of Higher Learning in Malaysia can further enhance the 12th learning outcome of ‘Laporan Hala Tuju 2’ to ‘Demonstrate Behaviour Consistent with Professional Ethics and Social Responsibility’ and the requirement of International Federation of Accountant’s IES 4 of ‘Professional Values, Ethics and Attitudes’. Gender and academic performance’s influence on ethical sensitivity may give some insights to the prospective employer on the selection criteria of future accountants and auditors, with regards to ethical conduct.